Disarmed : The Missing Movement for Gun Control in America - Goss, Kristin A., 1965- (Book collections on Project MUSE., 2009)
More than any other advanced industrial democracy, the United States is besieged by firearms violence. Each year, some 30,000 people die by gunfire. Over the course of its history, the nation has witnessed the murders of beloved public figures; massacres in workplaces and schools; and epidemics of gun violence that terrorize neighborhoods and claim tens of thousands of lives. Commanding majorities of Americans voice support for stricter controls on firearms. Yet they have never mounted a true national movement for gun control. Why? Disarmed unravels this paradox. Based on historical archives, i.